Predicting chelonia mydas nests survivability rates with use of machine learning techniques: applying machine learning techniques on conservation data – case study - Calçada, David Tiago (2020)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence